Comparison Between Continuous Buried Suture and Interrupted Buried Suture Methods for Double Eyelid Blepharoplasty. Issue 7 (October 2015) - Baek, Ji Sun; Ahn, Jung Hyo; Jang, Sun Young; Chee, Elaine; Jang, Jae Woo
Abstract : Purpose: The objective of this study was to compare the surgical outcomes between interrupted and continuous buried suture methods in double eyelid blepharoplasty in Koreans. Methods: Medical records of 204 patients (392 eyes) who underwent double eyelid operation by buried suture method and who were followed up for at least more than 3 months were reviewed. Patients were divided into 2 groups according to the buried suture method; an interrupted group (88 patients) and a continuous group (116 patients). Results: The rate of loss of formed double eyelid is 19.3 % (17 of 88 patients) in interrupted buried method and 8.6 % (10 of 116 patients) in continuous group ( P = 0.026). One patient experienced an exposure of suture knot in a continuous group, whereas 5 patients experienced an exposure of suture knot and 1 patient suffered from granuloma in an interrupted group ( P = 0.021). Conclusions: The continuous buried suture method has a lower rate of the loss of double folds and less complication than the interrupted buried suture method for double fold formation in Koreans.